2012
DOI: 10.1371/journal.ppat.1002548
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Innate Immune Priming in Wolbachia-Mediated Dengue Interference

Abstract: The non-virulent Wolbachia strain wMel and the life-shortening strain wMelPop-CLA, both originally from Drosophila melanogaster, have been stably introduced into the mosquito vector of dengue fever, Aedes aegypti. Each of these Wolbachia strains interferes with viral pathogenicity and/or dissemination in both their natural Drosophila host and in their new mosquito host, and it has been suggested that this virus interference may be due to host immune priming by Wolbachia. In order to identify aspects of the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
330
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 291 publications
(347 citation statements)
references
References 40 publications
13
330
2
2
Order By: Relevance
“…quito Aedes aegypti in Australia and reached near fixation within a few months (38). This is important because Wolbachia has been shown to prime the mosquito innate immune system, thus limiting the ability of pathogens such as dengue virus, Chikungunya virus, and Plasmodium to replicate in mosquito cells (39,40). Limiting the replication of dengue virus in the mosquito vector was shown to be possible using host microRNAs that manipulate host gene expression (41).…”
Section: Figmentioning
confidence: 99%
“…quito Aedes aegypti in Australia and reached near fixation within a few months (38). This is important because Wolbachia has been shown to prime the mosquito innate immune system, thus limiting the ability of pathogens such as dengue virus, Chikungunya virus, and Plasmodium to replicate in mosquito cells (39,40). Limiting the replication of dengue virus in the mosquito vector was shown to be possible using host microRNAs that manipulate host gene expression (41).…”
Section: Figmentioning
confidence: 99%
“…55 Though the fundamental mechanism involved in viral blocking, demonstrated in both Drosophila and Aedes, does not seem to be dependent on the upregulation of the immune effectors, it is likely that Wolbachia-associated immune priming in mosquitoes can enhance the virus blocking phenotype. 56,57 Furthermore, microbial gut flora of mosquito interacts with host immune system to determine the outcome of host-pathogen interactions, 28,58 and evidence is emerging on how temperature can affect the presence and quantity of symbionts in insect's gut to influence host fitness. 59 How different temperature regimes can affect DENV blocking by possibly changing host immunity and its gut microbiota also needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the host's innate immune system by Wolbachia has been suggested as one mechanism causing pathogen interference in both naturally infected Drosophila and transinfected A. aegypti mosquitoes (Moreira et al, 2009;Bian et al, 2010;Rances et al, 2012;Wong et al, 2015), but the impact on Wolbachia itself has remained unclear. In this work, we have shown that both the IMD and Toll pathways in A. aegypti are triggered by introduction of the bacterium Wolbachia wAlbB.…”
Section: Discussionmentioning
confidence: 99%